Comparative Structural Seismic Performance of a 10-Story Commercial Building Using Lightweight Precast Concrete Panels and Lightweight Brick Wall Systems - Tanjung, Naisha Elvira; Imanuel, Ivan; Bali, Ika (PRESUNIVE CIVIL ENGINEERING JOURNAL, 2025)
This study presents a comparative seismic performance analysis of a 10-story commercial building in North Jakarta, an area characterized by high seismicity and challenging geotechnical conditions. Two identical structural models were analyzed using ETABS v2022: one using a lightweight precast concrete panel system (JOE Green X3) and the other using a conventional Autoclaved Aerated Concrete (AAC) lightweight brick system. The aim is to compare the seismic structural performance of the analysis, based on the response spectrum method in accordance with SNI 1726:2019, revealed that the precast concrete panel system, was 14.4% lighter than the AAC lightweight bricks system when accounting for its full installed weight, including plaster and bracing columns. It resulted in a shorter fundamental period (0.412 s) compared to 0.453 s of the AAC lightweight brick system. However, the seismic base shear forces are nearly identical due to compensating effects in the site-specific response spectrum. Although both systems meet the deflection limits mandated by regulations, their performance is direction-dependent. This study concludes that the substantial reduction in total mass of the precast panel system provides a shorter vibration period but comparable seismic performance to the AAC lightweight brick system.